Synthesis and optical properties of pyrrolidinyl peptide nucleic acid carrying a clicked Nile red label - Yotapan, Nattawut; Charoenpakdee, Chayan; Wathanathavorn, Pawinee; Ditmangklo, Boonsong; Wagenknecht, Hans-Achim; Vilaivan, Tirayut (Beilstein Journal of Organic Chemistry, 2014)
DNA or its analogues with an environment-sensitive fluorescent label are potentially useful as a probe for studying the structure and dynamics of nucleic acids. In this work, pyrrolidinyl peptide nucleic acid (acpcPNA) was labeled at its backbone with Nile red, a solvatochromic benzophenoxazine dye, by means of click chemistry. The optical properties of the Nile red-labeled acpcPNA were investigated by UV–vis and fluorescence spectroscopy in the absence and in the presence of DNA. In contrast to the usual quenching observed in Nile red-labeled DNA, the hybridization with DNA resulted in blue shifting and an enhanced fluorescence regardless of the neighboring bases. More pronounced blue shifts and fluorescence enhancements were observed when the DNA target carried a base insertion in close proximity to the Nile red label. The results indicate that the Nile red label is located in a more hydrophobic environment in acpcPNA–DNA duplexes than in the single-stranded acpcPNA. The different fluorescence properties of the acpcPNA hybrids of complementary DNA and DNA carrying a base insertion are suggestive of different interactions between the Nile red label and the duplexes.
Keywords: click chemistry; deoxyribonucleic acid; DNA bulge; fluorescence; nucleic acids; solvatochromism